The prevalence of nursing caries in Davangere preschool children and its relationship with feeding practices and socioeconomic status of the family - Tyagi R (Wolters Kluwer Medknow Publications, 2008)
The aim of the present study was to find the prevalence of nursing caries in Davangere preschool children and its relationship with feeding practices and socioeconomic status of the family. Materials and Methods: A total of 813 children aged 2-6 years were screened for the present study from randomly selected three kindergarten schools each from Government, Government aided, and private managements. Clinical examination was done inside the respective schools. At the time of examination, a proforma was filled for each child comprising of DFS index. The questionnaire by Winter et al. was modified and used in this study. The completed proformas were statistically analyzed to find if any correlation existed between the nursing caries to the feeding practices and socioeconomic status of the family. Results: Duration of breastfeeding increases the number of children with nursing caries and the mean DFS. There is a strong and significant relationship between the severity of nursing caries and the degree of feeding abuse. Children from low socioeconomic status have increased early childhood caries. Conclusion: The prevalence of nursing caries was 19.2% in Davangere preschool population. Nursing caries were more in children who were taking a feeding bottle to bed at night and were increasingly seen in large families and lower socioeconomic groups.